Analysing White Supremacy Ideology and Strategies for Its Prevention (Jurnal Lemhannas RI, 2024)
Purpose: Mass shootings in America have increased significantly in recent decades. Half of all incidents have occurred since 2000, with one-third since 2010. Victim numbers have also risen, from an average of 8 deaths per year in the 1970s to 51 per year in the 2010s. Data reveal that most perpetrators are white males, and that a culture of violence and easy access to firearms are key drivers. This study investigates why many white men commit mass shootings, using the Buffalo shooting as a case study.Study Design/Methodology/Approach: This research adopts a qualitative design, using a case study approach to examine events and individual action in detail.Findings: Mass shootings are rooted in social pathologies within American society, exacerbated by the ideology of white supremacy. This ideology, born from frustration with progress in racial and gender equality, channels anger towards individuals perceived as foreign. Originality/Value: The study underscores the need for risk management in firearm ownership to prevent misuse. By providing an in-depth analysis of a specific case, it enriches existing literature on supremacist ideology and offers insights into its prevention.
Keywords: White Supremacy; Firearms; Mass Shootings; Violence; Ideology